Chronic Energy Deficiency Associated with Body Mass Index of Adolescent Girls - Titaley, Christiana; Ardianto, Anggih Cipta; Zawawi, Wa Ode Meutya; Asmin, Elpira; Tahitu, Ritha; Sara, Liyani S.; van Affelen, Zadrach; Tando, Yudhie D.; Titaley, Christiana R.; , Ricky N.D.C Ratu; Abbas, Hasriwiani Habo (Window of Health : Jurnal Kesehatan, 2024)
Chronic Energy Deficiency (CED) is a nutritional issue that poses a threat to adolescents in Indonesia, particularly to adolescent girls. According to the 2018 Basic Health Survey (Riskesdas), the proportion of CED among adolescent girls in Indonesia was 36.3%. This study aimed to identify the factors associated with CED among adolescent girls in the catchment area of Poka-Rumah Tiga, Ambon City. The study was conducted in August 2022 and used a cross-sectional approach with total sampling. The respondents were students aged 15-19 years from three high schools/equivalents in the catchment area of Poka-Rumah Tiga Health Center (SMKN 5 Ambon, SMAN 3 Ambon, and MA Al-Mabrur), with a total of 441 respondents. CED was determined based on the mid-upper arm circumference size being less than 23.5 cm. Logistic regression analysis was used to identify factors associated with CED in adolescent girls. Of the 441 adolescent girls who participated in this study, 45.80% were found to have CED. The odds of CED were lower in adolescent girls with normal BMI (18.5-22.9 kg/m2) (OR=0.09; 95%CI: 0.05-0.15; p less than 0.001) and overweight (≥23 kg/m2) (OR=0.01; 95%CI: 0.00-0.07; p less than 0.001) compared to those who were underweight (BMI less than 18.5 kg/m2). This study highlights the importance of conducting nutrition-specific and nutrition-sensitive interventions for adolescent girls. This includes raising the awareness and knowledge of adolescent girls, family members, and school teachers regarding the importance of balanced nutrition to reduce CED.